(untitled) (Economic studies journal, 2021)
Abstract This paper aims at estimating the gap between the actual GDP and potential GDP to find the GDP gap for the Libyan economy during 1962-2017. Hedrick-Prescott procedure is used to find the potential GDP in order to eliminate the sort-run fluctuations that may occur in GDP, which keeps just the long-run variations. The results discovered that GDP gap is strongly associated with the oil product which was positive gap during the massive oil product periods, while it was negative gap during the oil crisis. Also, this paper found that, the negative gap in the recent years has witnessed returning to the equilibrium path after the recovery in the oil sector. Key words: Potential GDP, actual GDP, GDP gap